ANALISIS PERBANDINGAN METODE PERAMALAN (FORECASTING) PENJUALAN MOTOR LISTRIK PADA CV SANTOSA ABADI MOTOR PELAIHARI - Indriani Dwi Lestari; Bella Puspita Rininda; Widiya Astuti Alam Sur; Marliza Noor Hayatie (LPPM Universitas Ibnu Sina, 2025)
The aim of this study is to identify the most accurate and effective forecasting method for CV. Santosa Abadi Motor Pelaihari in predicting the sales of electric motor products for the upcoming period. This research is a descriptive quantitative study utilizing secondary data, consisting of electric motor product sales data from 2023 through January-June 2024, obtained from the Administration department of CV Santosa Abadi Motor Pelaihari. The analysis involves comparing three forecasting methods: Trend Moment, Semi Average, and Least Square, and evaluating the accuracy of each method using the Mean Absolute Percentage Error (MAPE). The results indicate that the Trend Moment method yields a forecasting error percentage of 71%, the Semi Average method results in 23%, and the Least Square method shows 28%. Based on these findings, it can be concluded that the Semi Average method is more suitable for forecasting electric motor sales at CV Santosa Abadi Motor Pelaihari.